Journey to the other side of the brain: asymmetry in patients with chronic mild or moderate traumatic brain injury - David E Ross; John D Seabaugh; Jan M Seabaugh; Claudia Alvarez; Laura Peyton Ellis; Christopher Powell; Christopher Reese; Leah Cooper; Katherine Shepherd; for the Alzheimer's Disease Neuroimaging Initiative (Concussion)
Aim: Patients with chronic mild or moderate traumatic brain injury have some regions of brain atrophy (including cerebral white matter) but even more regions of abnormal brain enlargement (including other cerebral regions). Hypothesis: Ipsilateral injury and atrophy cause the eventual development of contralateral compensatory hypertrophy. Materials & methods: 50 patients with mild or moderate traumatic brain injury were compared to 80 normal controls (n = 80) with respect to MRI brain volume asymmetry. Asymmetry-based correlations were used to test the primary hypothesis. Results: The group of patients had multiple regions of abnormal asymmetry. Conclusion: The correlational analyses supported the conclusion that acute injury to ipsilateral cerebral white matter regions caused atrophy, leading eventually to abnormal enlargement of contralateral regions due to compensatory hypertrophy.